Lexical Retrieval Difficulties in the L1 of Lithuanians in Ireland - Vaisėtaitė, Eglė (Lietuvių kalba, 2021)
The article describes the study of the Irish Lithuanian (IL) L1 lexical attrition. Several indications can show lexical attrition: vocabulary reduction, use of hypernyms instead of hyponyms, code switching, and hesitation markers. These signs indicate that the person is having difficulty retrieving words from memory. The article analyzes 30 IL speech examples (recordings of picture description) while focusing on the hesitation markers (pauses, corrections, repetitions, etc.) and the units of lexical expression. The study involves first-generation emigrants who left Lithuania at the age of 12 or older and have lived in Ireland for 5 years or more. The data of the target group are compared with the data of the control group – Lithuanians living in Lithuania (LL). The significance of the results is confirmed by applying T test.During the study, informants were asked to describe two pictures. The results show that there were more hesitation markers in IL speech rather than in LL speech (p = 0.000). In addition, less relevant units of lexical expression were used in IL rather than in LL speech (p = 0.002). Such results suggest that the target group experience difficulties retrieving words from memory and this could mean that their L1 lexicon is facing attrition. It also turned out that the picture related to private life situations was described more fluently than the picture related to public life situations.
Keywords: L1; lexical attrition; lexical access; hesitation markers; lexical expression